The policy as repudiation factors of adopting cloud computing in university administration - Badie, Nasrin (2013)
Cloud computing (CC) technology can be described as the next generation of Information technology for companies, educational institutions and governmental agencies; which provides easy and affordable access to state of the art technology; IT, technological application and services. Due to the growing needs for information technology (IT) and the current dwindling global financial stability, many higher education institutes including universities, are facing problems in providing the essentials of IT supports for administrative, educational, and research activities. However, CC is rarely implemented in universities in Malaysia. This research thus aims to find out the causal factor for the poor implementation and usage of CC in Malaysia universities. To achieve our aim, CC published works was reviewed to identify the staff positions as well as their required services. The outcomes of the review were applied to find out the models, services, and applications that are available in educational environments. Afterwards, an explorative case study was used to explore the factors that have caused the negligence of CC applications at universities. A semi-structured interview was used to collect data and samples were randomly chosen among administrators, IT staffs, technicians and clerks at one of the biggest public university in Malaysia. The data were analyzed both quantitatively and qualitatively. The findings showed that policy is the main reason to reject of using CC in administrative activities. Thus, with amendment of the existing policy, authorities can benefit from CC and as well as prevent the risk associated with CC.